Deficiência, raça e gênero: análise de indicadores educacionais brasileiros - Pereira, Michelle Melina Gleica Del Pino Nicolau (2016)
This study aimed to analyze the educational indicators of people with disabilities in relation to gender and race. Sources of data collection were the Demographic Census (IBGE 2010), on the incidence of population and the School Census (MEC, INEP, 2012) with regard to the enrollment of students with visual impairments, hearing impairments, physical and intellectual in the year 2012, in basic education, by type of schooling and education step, nationwide and distributed by geographic regions. The data were submitted to hypothesis tests, Z based on the normal distribution, for two independent samples, Chi-square and coefficient C of Cramér and analyzed on the basis of the contributions of Bourdieu (1983, 1998 and 2011), Louro (2003) and Munanga (1986, 1996), about social divisions and relations of gender and race inequality in order to investigate other social tags in the analysis of the processes of education of these students , disregarded by educational research, as well as in those of Cury (2002, 2005 and 2008), Skrtic (1996, 2011) and Bueno (1999, 2008) on inclusive policies and equal opportunities. We conclude that the combination between the categories of gender and race intensify the inequality in access to education of persons with disabilities: increased enrollment of male white students, a fact that also reproduces in the segregated school; the black women students with disabilities have greater disadvantage of access to schooling; the white men have better possibilities for school progression, with the largest number of enrollments in high school